Immunoglobulin superfamily members encoded by viruses and their multiple roles in immune evasion. Issue 5 (9th May 2017) - Farré, Domènec; Martínez‐Vicente, Pablo; Engel, Pablo; Angulo, Ana
Abstract : Large DNA viruses acquire new genes by horizontal gene transfer from host genomes. After evolutional adaptation, the expression of these viral homologs in infected cells contributes to viral immune evasion. We review homologs of immunoglobulin superfamily (IgSF) members encoded by herpesviruses, poxviruses and adenoviruses, and their immunodulatory roles. Abstract : Pathogens have developed a plethora of strategies to undermine host immune defenses in order to guarantee their survival. For large DNA viruses, these immune evasion mechanisms frequently rely on the expression of genes acquired from host genomes. Horizontally transferred genes include members of the immunoglobulin superfamily, whose products constitute the most diverse group of proteins of vertebrate genomes. Their promiscuous immunoglobulin domains, which comprise the building blocks of these molecules, are involved in a large variety of functions mediated by ligand‐binding interactions. The flexible structural nature of the immunoglobulin domains makes them appealing targets for viral capture due to their capacity to generate high functional diversity. Here, we present an up‐to‐date review of immunoglobulin superfamily gene homologs encoded by herpesviruses, poxviruses, and adenoviruses, that include CD200, CD47, Fc receptors, interleukin‐1 receptor 2, interleukin‐18 binding protein, CD80, carcinoembryonic antigen‐related cell adhesion molecules, and signaling lymphocyte activation molecules. We discuss their distinct structural attributes, binding properties, and functions, shaped by evolutionary pressures to disarm specific immune pathways. We include several novel genes identified from extensive genome database surveys. An understanding of the properties and modes of action of these viral proteins may guide the development of novel immune‐modulatory therapeutic tools.